Ag2Mo2O7: an oxide solid-state Ag+ electrolyte. Issue 6 (26th January 2022) - Yan, Weixin; Zhu, Dongmei; Wang, Zhaofeng; Xia, Yunhao; Gui, Dong-Yun; Luo, Fa; Wang, Chun-Hai
Abstract : Ag2 Mo2 O7 is an oxide solid-state Ag + electrolyte with the conductivity ∼5 × 10 −4 S cm −1 at 450 °C and carrier activation energy 0.88(3) eV. Abstract : Ag2 Mo2 O7 powders and micro-crystals were prepared at 400 °C for 24 h and 500 °C for 6 h using solid-state reactions. The Ag2 Mo2 O7 samples crystalized in a triclinic P 1̄ space group with the cell parameters a = 6.0972(1) Å, b = 7.5073(1) Å, c = 7.6779(2) Å, α = 110.43(1)°, β = 93.17(1)°, γ = 113.51(1)°, and V = 294.17(1) Å 3 from Rietveld refinements. Ag2 Mo2 O7 powder is homogeneous with size of 2–8 μm and the ceramic pellets are in good sintering conditions with a relative density ∼93%. The indirect band gaps E g (i) of Ag2 Mo2 O7 from reflectance measurements and DFT calculations are 2.63(1) and 1.80 eV. The vibrational modes of Ag2 Mo2 O7 were investigated by first-principles (DFT) calculations and Raman spectrum measurements with 24 of 33 predicted Raman modes recorded. According to DOS analyses, the valence bands (VB) of Ag2 Mo2 O7 are mainly constituted of O-2p and Ag-4d orbitals, while the conduction bands (CB) are mainly composed of Mo-4d and the O-2p orbitals. Regarding the impedance analysis, Ag2 Mo2 O7 is a silver oxide ion electrolyte with a conductivity of ∼5 × 10 −4 S cm −1 at 450 °C. The carrier activation energy of Ag2 Mo2 O7 is 0.88(3) eV from the temperature dependent conductivity measurements.